Effects of the in-utero dicyclohexyl phthalate and di-n-hexyl phthalate administration on the oxidative stress-induced histopathological changes in the rat liver tissue correlated with serum biochemistry and hematological parameters - Aydemir, Duygu; Aydogan-Ahbab, Mufide; Barlas, Nurhayat; Ulusu, Nuriye Nuray (Frontiers in Endocrinology, 2023)
Phthalates are widely used as plasticizers in the industry and are found in cosmetics, food and drink packaging, drugs, toys, households, medical devices, pesticides, personal care products, and paints. Phthalates exert endocrine disrupting and peroxisome proliferator effects in humans and wildlife associated with the pathogenesis of various diseases, including diabetes, obesity, infertility, cardiovascular diseases, metabolic syndrome, and cancer. Since phthalates are metabolized in the liver, which regulates the body's energy metabolism, long or short-term exposure to the phthalates is associated with impaired glucose, lipid, and oxidative stress metabolisms contributing to liver toxicity. However, the impact of in-utero exposure to DHP and DCHP on liver metabolism has not been studied previously. Thus, in this study, we evaluated serum biochemistry parameters, hematological markers, histopathological changes, and oxidative and pentose phosphate pathway (PPP) metabolisms in the liver following in-utero DHP and DCHP administration, respectively, in male and female rats. We found increased relative and absolute liver weights and impaired triglyceride, alanine transaminase (ALT), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP) levels upon dicyclohexyl phthalate (DCHP) and di-n-hexyl phthalate (DHP). Histopathological changes, including congestion, sinusoidal dilatation, inflammatory cell infiltration, cells with a pyknotic nucleus, lysis of hepatocytes, and degeneration of hepatic parenchyma have been observed in the liver samples of DHP and DCHP dose groups. Moreover, increased glutathione s-transferase (GST), glucose 6-phosphate dehydrogenase (G6PD), and glutathione reductase (GR) activities have been found in the liver samples of DHP and DCHP-treated rats associated with impaired pentose phosphate pathway (PPP) and oxidative stress metabolism. First time in the literature, we showed that in-utero exposure to DHP and DCHP causes liver damage associated with impaired oxidative stress metabolism in male and female rats. Our data may guide researchers and governments to regulate and restrict phthalates in industrial products.